The Prospect of Accelerated Program on Economic and Social Development of Underdeveloped Region - Hanafi Dahlan (Jurnal Penelitian Kesejahteraan Sosial, 2014)
The condition of Jetis Village, between pre and post program of accelerated social and economy development of underdeveloped regions (P2SEDT), is different. This research is done to know the continuity of the program in improving and strengthening society self-sustaining to grow by them shelves, especially poor families in the context of continuity program. This research uses a case study method, a research that done deeply related to research subjects. This research is done in Jetis Village, Gunungkidul Regency, Yogyakarta Special Territory, was categorized as underdeveloped village. Data are gathered through deep interview and observation. The research finds that the relation pattern between empowerment process, targeted group, and level of program continuity, is participative enough and able to empower targeted group awareness, and there is a relation between P2DST fund rate of return given to targeted group. The beneficiary got by targeted group is enable to enhance economically, that can be seen in the development of village management and healthy settlement, and the continuation of the program in Jetis Village that enable to empower targeted group to self-sustainability, manifested through their participation and group awareness. It is recommended that KPPSB guidance should be intensified since the beginning of the program, stressed on participation aspect and to grow group awareness to keep the continuity of the program.